2016
DOI: 10.3171/2015.7.jns15132
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative external tissue expansion for complex cranial reconstructions

Abstract: OBJECTIVE Reconstruction of large solitary cranial defects after multiple craniotomies is challenging because scalp contraction generally requires more than simple subcutaneous undermining to ensure effective and cosmetically appealing closure. In plastic and reconstructive surgery, soft tissue expansion is considered the gold standard for reconstructing scalp defects; however, these techniques are not well known nor are they routinely practiced among neurosurgeons. The authors here describe a simple external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…A retrospective, single-center study of six patients underwent definitive cranioplasty with preoperative CETE reported an average 16% increase in scalp surface area (range, 6.6–35.0%), resulting in all patients having adequate tissue for tension-free closure. 37 The DermaClose device was well tolerated, and all patients were satisfied with the cosmetic outcome. No instances of delayed wound closure, infection, dermatitis, or cerebrospinal fluid leakage were reported.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…A retrospective, single-center study of six patients underwent definitive cranioplasty with preoperative CETE reported an average 16% increase in scalp surface area (range, 6.6–35.0%), resulting in all patients having adequate tissue for tension-free closure. 37 The DermaClose device was well tolerated, and all patients were satisfied with the cosmetic outcome. No instances of delayed wound closure, infection, dermatitis, or cerebrospinal fluid leakage were reported.…”
Section: Discussionmentioning
confidence: 84%
“…The device was applied an average of 238 days (standard deviation = ±60 days) after craniectomy, and the surgeon adjusted the device over the following 7–10 days. 37 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other techniques described in the literature to correct sequelar alopecia of the scalp include external tissue expansion 18 and hair grafting in the alopecia zone. 19 In our experience, the outcome of hair grafting is very disappointing in large zones of scar tissue, but this technique can be attempted in small zones, such as enlarged scars.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%